Numerical simulation of the blade channel vortices in a Francis turbine runner. Issue 2 (18th April 2017) - Zhou, Lingjiu; Liu, Meng; Wang, Zhengwei; Liu, Demin; Zhao, Yongzhi
Abstract : Purpose: This study analyzes the blade channel vortices inside Francis runner with a particular focus on the identification of different types of vortices and their causes. Design/methodology/approach: A single-flow passage of the Francis runner with refined mesh and periodic boundary conditions was used for the numerical simulation to reduce the computational resource. The steady-state Reynolds-averaged Navier–Stokes equations closed with the k- ω shear–stress transport (SST) turbulence model were solved by ANSYS CFX to determine the flow field. The vortices were identified by the second largest eigenvalue of velocity. Findings: Four types of vortices were identified inside the runner. Three types were related to the inlet flow. The last one (Type 4) was caused by the reversed flow near the runner crown and had the lowest pressure inside the core near the runner outlet. Thus, in the blade channel vortex inception line, Type 4 vortex would appear earlier than the other three ones. Besides, the Type 4 vortex emerged from the crown and shed toward the blade-trailing edge. And its location moved from near the crown down to near the band when the unit speed increased or unit discharge decreased. Research limitations/implications: Although the refined mesh was used and the main vortices in the Francis runner were well predicted, the current mesh is not enough to accurately predict the lowest pressure in the channel vortex core. Practical/implications: This knowledge is instructive in the runner blade design and troubleshooting related to the channel vortex. Originality/value: This study gives an overview of the main observed blade channel vortices and their causes, and points out the important role the reversed flow plays in the formation of blade channel vortices. This knowledge is instructive in the runner blade design and troubleshooting related to blade channel vortices.